Comprehensive Geriatric Assessment: Addressing Unmet Healthcare Needs in Older Adults - Dimitriadou, Ioanna; Toska, Aikaterini; Eloranta, Sini; Mört, Susanna; Korsström, Nina; Lundberg, Anna; Häger, Magdalena; Melbarde-Kelmere, Agita; Circenis, Kristaps; Šteinmiller, Jekaterina; Skuladottir, Sigrun S.; Hjaltadóttir, Ingibjorg; et al. (MDPI, 2026)
This narrative review examines the Comprehensive Geriatric Assessment (CGA), a multidisciplinary approach used to evaluate and manage the health of older adults. CGA has been shown to improve functional status, reduce hospital readmissions, delay institutionalization, and lower mortality. Despite these benefits, systematic implementation remains limited. Major barriers include shortages in the workforce and resources, a lack of standardized protocols, and insufficient training in geriatric competencies. These challenges leave many older adults with unmet healthcare needs, particularly in chronic disease management, functional limitations, mental health, and social support. Nurses are well positioned to address these gaps because of their expertise in patient-centered care, care coordination, and chronic disease management. Strengthening geriatric nursing education and integrating CGA into routine nursing practice can improve outcomes for the aging population. Although CGA is often associated with hospital settings, its future lies in broader application. Digital solutions scheduled health assessments, workforce planning, and community- or home-based evaluations can make CGA more accessible. Policymakers, healthcare systems, and educational institutions must work together to develop policies that embed CGA within primary healthcare.